PROCESSING OF COAGULATION FLOCCULATION SEQUENCING BATCH REACTOR (SBR) IN KEBON AGUNG RIVER AS CLEAN WATER - Wildanum, Pinasthika Almira; Hendrasarie, Novirina (Journal of Environmental Engineering and Sustainable Technology, 2022)
River water treatment uses a Sequencing Batch Reactor (SBR) with cassava peel adsorbents, meranti wood powder, and PAC. After going through the Sequencing Batch Reactor, (SBR), it will give disinfection to reduce the levels of E. Coli and total coliform in the water. It is expected to be able to set aside levels of turbidity, color, TDS, taste, odor, total coliform, E.Coli, nitrate, nitrite, hardness, and organic matter (KMnO4). The river water to be treated comes from the coagulation-flocculation process. Making variations of HRT and adsorbent. The hydraulic retention time variations compared were 6, 9, and 12 hours. There are 3 reactors with 1 control reactor, which includes a control reactor without adsorbent and one with PAC adsorbent. The conditions chosen at the reaction stage are aerobic. The removal efficiency of the color parameter is 8.4%, the total coliform parameter is 94.6%, the parameter e.coli 95.2%, the nitrate parameter is 52.6%, the nitrite parameter is 14.3%, and the organic matter parameter is 7.8%. At the same time, the parameters have increased by 2%. The best HRT in reducing pollutant levels in this study was 12 hours HRT for the SBR reactor with cassava peel adsorbent sowing placement, 6 hours HRT for the SBR reactor with meranti wood powder adsorbent sowing placement, and 6 hours HRT for the SBR reactor with top placement PAC adsorbent. The best effectiveness of the Sequencing Batch Reactor (SBR) in treating Kebon Agung River water is by adding meranti wood powder adsorbent by placing sprinklers